2006
DOI: 10.1074/jbc.m607686200
|View full text |Cite
|
Sign up to set email alerts
|

Random Mutagenesis of the Complement Factor 5a (C5a) Receptor N Terminus Provides a Structural Constraint for C5a Docking

Abstract: The N terminus of G protein-coupled receptors has been implicated in binding to peptide hormones. We have used random saturation mutagenesis to identify essential residues in the N terminus of the human complement factor 5a receptor (C5aR). In a library of N-terminal mutant C5aR molecules screened for activation by C5a, residues 24 -30 of the C5aR showed a marked propensity to mutate to cysteine, most likely indicating that sulfhydryl groups at these positions are appropriately situated to form disulfide inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…Library Construction and Screening-Libraries of mutant C5aRs were generated as described previously (12,23). Briefly, the nucleotide sequence of the region of interest (NT or EC2) was flanked by silent restriction sites, then replaced by a noncoding "stuffer" sequence to prevent wild-type contamination of the library.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Library Construction and Screening-Libraries of mutant C5aRs were generated as described previously (12,23). Briefly, the nucleotide sequence of the region of interest (NT or EC2) was flanked by silent restriction sites, then replaced by a noncoding "stuffer" sequence to prevent wild-type contamination of the library.…”
Section: Methodsmentioning
confidence: 99%
“…2A). The seventh cysteine (Cys 27 ) has an outwardly directed side chain (29,30) that was previously used for disulfide trapping analysis (12). The data in our earlier study showed that in the receptor-ligand complex, Cys 27 of C5a is positioned close to residues 24 -30 of the C5aR.…”
Section: Generation Of Mutant C5a Ligands With Unpairedmentioning
confidence: 97%
See 3 more Smart Citations